Analysis of the Impact of Computer-Based Training on Air Traffic Services at Palembang Radar Service - Rivandi Sohuturon Sitorus; Gilang Trio Putra; Nunuk Praptiningsih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The provision of air traffic services requires Air Traffic Controllers (ATCs) to possess high levels of competence, particularly in mastering procedures, operating equipment, and making fast and accurate decisions. To maintain these competency standards, AirNav Indonesia implements various training programs, including Computer-Based Training (CBT). However, at Palembang Radar Service, a key issue remains the absence of clearly structured, comprehensive, and operationally specific CBT modules tailored to local radar operations. This study aims to analyze the influence of the Computer-Based Training (CBT) program on air traffic services at Palembang Radar Service. The research employed a descriptive-associative quantitative approach, using numerical data to examine the relationship between variables through statistical analysis. Data were collected from active ATC personnel using structured questionnaires and analyzed using correlation and hypothesis testing methods.